The α-cell in diabetes mellitus. Issue 12 (December 2018) - Gromada, Jesper; Chabosseau, Pauline; Rutter, Guy
Abstract Findings from the past 10 years have placed the glucagon-secreting pancreatic α-cell centre stage in the development of diabetes mellitus, a disease affecting almost one in every ten adults worldwide. Glucagon secretion is reduced in patients with type 1 diabetes mellitus, increasing the risk of insulin-induced hypoglycaemia, but is enhanced in type 2 diabetes mellitus, exacerbating the effects of diminished insulin release and action on blood levels of glucose. A better understanding of the mechanisms underlying these changes is therefore an important goal. RNA sequencing reveals that, despite their opposing roles in the control of blood levels of glucose, α-cells and β-cells have remarkably similar patterns of gene expression. This similarity might explain the fairly facile interconversion between these cells and the ability of the α-cell compartment to serve as a source of new β-cells in models of extreme β-cell loss that mimic type 1 diabetes mellitus. Emerging data suggest that GABA might facilitate this interconversion, whereas the amino acid glutamine serves as a liver-derived factor to promote α-cell replication and maintenance of α-cell mass. Here, we survey these developments and their therapeutic implications for patients with diabetes mellitus. Over the past 10 years, evidence has accumulated to suggest that α-cells are involved in the development of diabetes mellitus. This Review outlines our current understanding of α-cells and discusses how they could be targeted in the treatment of diabetes mellitus. Key points The mechanisms involved in the control of glucagon secretion in pancreatic α-cells have now been identified. The pancreatic α-cell has a role in the development of diabetes mellitus. Physiological and pharmacological activators and inhibitors of glucagon secretion might provide therapeutic targets. Single α-cell gene expression profiling in health and disease has resulted in new insights about the function of α-cells. Advances in understanding α-cell to β-cell reprogramming could lead to new therapeutic strategies for diabetes mellitus.